Qualitative Analysis of Systems of Itô Stochastic Differential Equations - Kulinich, G. L.; Pereguda О. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For inhomogeneous systems of Itô stochastic differential equations, we introduce the notion of local invariance of surfaces and the notion of local first integral. We obtain results that give the general possibility of finding invariant surfaces and functionally independent first integrals of stochastic differential equations.